ANALISIS PENGARUH CITRA MEREK, PERSEPSI KUALITAS DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN MINUMAN PENAMBAH TENAGA NON CAIR HEMAVITON JRENG DI KABUPATEN KENDAL THE EFFECT ANALYSIS OF BRAND IMAGE, QUALITY PERCEPTION AND PRICE TO BUYING DECISION ENERGY DR - Slamet Masudi, 09.05.51.0110; Kasmari, Kasmari (Students Journal of Economic and Management, 2014)
This research aim to analyze the effect of Brand Image, Quality Perception and Price to Buying Decison Hemaviton Jreng in Sentral Swalayan, Jl. Soekarno-Hatta No. 305, Kabupaten Kendal. The population in this research were consumers who had bought energy drink non liquid Hemaviton Jreng. But this research just took 100 consumers only as sample of the research. The sample method used accidental sampling method. This research used primary data which was collected by quotionaire. Then data was analyzed by multiple regression technique. Research result show that : (1). Brand Image had positive and significant effect to buying decison. (2). Quality Perception had positive and significant effect to buying decison. (3). Price had positive and significant effect to buying decison. Keywords: Brand Image, Quality Perception, Price, Buying Desicion